Identification of Indicators for Assessing Research-Extension-Farmers Linkage in Fisheries Sectors of Tripura - Yumlembam Jackie Singh,; Shekhar Nath,; Anil Datt Upadhyay,; Pachampalayam Shanmugam Ananthan,; Shivaji Dadabhau Argade,; Martina Meinam,; Huirem Bharati,; Shakir Ahmad Mir, (Indian Journal of Extension Education, 2023)
The study was conducted in Tripura from 2019 to 2022 to identify different indicators for linkage between research-extension-farmers in fisheries sectors. For selecting relevant indicators that are responsible for establishing linkage among the researchers, extension personnel, and farmers, different published documents, reports, and secondary sources were reviewed for the study. The indicators identified for establishing linkage were pooled and a comprehensive list of indicators was prepared. There were 53 indicators that were kept under different categories in the pooled list using the three-point continuum; Most Relevant (MR), Relevant (R), and Not Relevant (NR). After obtaining the judges' opinions, the relevancy score for each indicator was worked out using the relevancy percentage. The 24 indicators having an average relevancy percentage of more than 75 were finally selected for the study. Conducting need-based training (92.78%, I), Regular contact with farmers (92.12%, II), and Assessing the outcome and impact of training attended (91.35%, III) were few of the important indicators identified in the study.